Blindness and children an individual differences approach - Warren, David H. (Cambridge University Press, 1994)
The book is a summary and interpretation of the research literature on infants and children with visual impairments. It concludes that many aspects of 'delayed' development are not the result of visual impairment itself, but rather of environmental variables that tend to accompany visual impairment. Thus many of the typical developmental delays may be ameliorated or avoided by the appropriate structuring of the child's experiences. The book is developmentally oriented and treats all of the major areas of child development. The author makes the premise that a truly useful body of knowledge about the development of children with visual impairments must not just characterize normative development, but must account for the factors that are associated with relatively good or poor developmental progress. Existing research literature is searched for evidence of variables that may account for individual differences, particularly variables related to the child's several environments
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Blind children; Children with disabilities / Development; Kind; Blindheit; Entwicklung